The tragedy of U.S. foreign policy how America's civil religion betrayed the national interest - McDougall, Walter A. 1946- (Yale University Press, 2016)
A fierce critique of civil religion as the taproot of America's bid for global hegemonyPulitzer Prize-winning historian Walter A. McDougall argues powerfully that a pervasive but radically changing faith that "God is on our side" has inspired U.S. foreign policy ever since 1776. The first comprehensive study of the role played by civil religion in U.S. foreign relations over the entire course of the country's history, McDougall's book explores the deeply infused religious rhetoric that has sustained and driven an otherwise secular republic through peace, war, and global interventions for more than two hundred years. From the Founding Fathers and the crusade for independence to the Monroe Doctrine, through World Wars I and II and the decades-long Cold War campaign against "godless Communism," this coruscating polemic reveals the unacknowledged but freely exercised dogmas of civil religion that bind together a "God blessed" America, sustaining the nation in its pursuit of an ever elusive global destiny.